Testis maturation stages of mud crab (Scylla olivacea) broodstock on different diets - Mhd Ikhwanuddin,; Ghazali Azmie,; Siti Fatimah Nahar,; Wee, Wendy; Mohamad N Azra,; Ambok-Bolong Abol-Munafi, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The aim of this study was to investigate how various diets influence testis maturation stages in mud crab (Scylla olivacea) broodstock. Morphological and histological assessments were performed in triplicate (10 male crabs each). Daily, subject crabs were fed a squid (Loligo sp.) and a fish (Decapterus sp.) diet at 5-10% of body weight. Diets were analyzed following methods from the Association of Analytical Communities (AOAC). In comparison to control (wild) crabs, the two diets generally did not cause significant differences (p>0.05) in body weight, carapace width and gonadosomatic index (GSI), except in the GSI of squid-fed crabs (p<0.05). At the end of the experiment, crabs that reached Stage 3 testis maturation included were 6 fish-fed individuals and 23 squid-fed individuals. Additionally, differences in crude protein and fat levels across diets influenced the nature of male gonadal development. In conclusion, a squid diet was sufficient to induce Stage 3 testis maturation in Scylla olivacea within 60 days of culture. Our results prove the usefulness in developing appropriate feeding regimes for male Scylla olivacea broodstock.